High Order Thinking Skill (Hots) dalam Pembelajaran Membaca di SMK Tiwikrama Mamuju, Apakah Efektif? - Tolayuk, Abner (Jurnal Ilmiah Multidisiplin Amsir, 2024)
This study aims to determine the effectiveness of the implementation of High Order Thinking Skill (HOTS) in improving the reading skills of grade XI students at SMK Tiwikrama. HOTS is a high-level thinking approach that involves analysis, evaluation, and creation of new information. The research method used is a quantitative method with an experimental design. The population of this study was all grade XI students at SMK Tiwikrama with a total of 24 students, who were also the research sample. The instrument used was a reading test consisting of 15 multiple-choice questions. This study was conducted in three stages, namely pre-test, treatment with the HOTS method for six meetings, and post-test. The results showed that the average pre-test score of students was 65, while the average post-test score increased to 82. The results of the t-test showed a significant difference between the pre-test and post-test scores, which proved that the implementation of the HOTS method was effective in improving students' reading skills. The main factors contributing to this improvement were the interactive learning approach, critical thinking exercises, and discussions and reflections during learning. Thus, the HOTS method is recommended to be applied in reading learning to improve students' understanding of the text in depth.